An in Vitro Study to Evaluate Antibacterial Effect Thymus Vulgaris Essential Oil Against Porphyromonas Gingivalis in Kurdistan– Iraq - Hama Rash A1 , Kareem S2 , Hamaamin H 3 , Qadr K3 , Salih S4, Azeez S2 , Sha A5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Purpose: Porphyromonas gingivalis is a keystone among perio-pathogengenic bacteria to initiate periodontitis and treatment is better when the periodontal pathogens including Porphyromonas gingivalis are totally eliminated. The essential oil of Thymus vulgaris has many bioactive constituents having antimicrobial activity against many bacteria. This study investigates the antibacterial effect of this extracts against Porphyromonas gingivalis. Methods: Sub gingival plaque samples were collected from individuals having periodontitis with the probing pocket depth of at least 6mm; Conventional microbiological tests and molecular technique used for confirmation of Porphyromonas gingivalis, hydrodistillation method was used for extraction of essential oil. Antibacterial activity of the extract against Porphyromonas gingivalis has been determined by using two fold serial dilution method to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Result: the essential oil extracted from Thymus vulgaris demonstrated antimicrobial effect against Porphyromonas gingivalis growth. Conclusion:The extract was able to demonstrate inhibitory and bactericidal activity against Porphyromonas gingivalis. Further studies should focus on the use of Thymus vulgaris essential oil in the treatment of periodontitis.